The cooperativity and allosteric inhibition of Escherichia coli phosphofructokinase depend on the interaction between threonine-125 and ATP. - Auzat, I (1994)
During the reaction catalyzed by the phosphofructokinase (EC 2.7.1.11) from Escherichia coli, the phosphoryl group transferred from ATP interacts with Thr-125 [Shirakihara, Y. & Evans, P. R. (1988) J. Mol. Biol. 204, 973-994]. The replacement of Thr-125 by serine changes the saturation by fructose 6-phosphate from cooperative to hyperbolic and abolishes the allosteric inhibition by phosphoenolpyruvate. The same changes, a saturation by fructose 6-phosphate that is no longer cooperative and an activity that is no longer inhibited by phosphoenolpyruvate, are observed with wild-type phosphofructokinase when adenosine 5'-[gamma-thio]triphosphate is used instead of ATP as the phosphoryl donor. These two perturbations of the ATP-Thr-125 interaction lead to the suppression of both the allosteric inhibition by phosphoenolpyruvate and the cooperativity of fructose-6-phosphate saturation, as if replacing the neutral oxygen of ATP by sulfur or removing the methyl group of Thr-125 had "locked" phosphofructokinase in its active conformation. The geometry of this ATP-Thr-125 interaction and/or the presence of the methyl group on the beta-carbon of Thr-125 are crucial for the regulatory properties of phosphofructokinase. This interaction could be a hydrogen bond between the neutral oxygen of the gamma-phosphate of ATP and the hydroxyl group of Thr-125.